The presence of exchange : GIFT in artistic research and beyond - (:unkn) unknown (Taideyliopiston Kuvataideakatemia, 2025)
This publication integrates empirical research, theoretical and fictional texts, art objects and artistic research to a nuanced and diverse understanding of the gift. We have brought together academic scholars and artist-researchers to interrogate existing and projected knowledges about the gift-concept. The Presence of Exchange delves into how artist-researchers conceptualise, materialise, and articulate the idea of gift - its role in society and in our lives. Eleven authors and author groups compile thoughts and ideas expressed in and through artistic practices. They speculate from artistic perspectives on gift economy, gift as an invitation, as a bond in relationships, entanglements and love, gift as a test and especially as a form of presence in exchange.
The Presence of Exchange – GIFT in Artistic Research and Beyond --- Relational Painting: A Chain of Encounters and Possibilities / Mirimari Väyrynen -- Shining a Light on the Gâteau Vivant - Structural Colour, Art, Perception, Capital and the Flavobacteria Presentedas a Gift / Laura Beloff & Katri Naukkarinen -- Souvenir of the 'me' / Cynthia Blanchette -- Gift of Inheritance: What is a Gift that One Cannot Experience? / Aurora Del Rio -- Denise Ann Darvall's Heart / Nina Liebenberg -- What Remains: Translating the Absence-Presence of Waste into Video Art / Sonja Lampinen, Olli Pyyhtinen & Niina Uusitalo -- Blankets, Dust and Larch Tree Needles – Reflections on Exchange / Denise Ziegler, Niilo Rinne -- Lahja yhteisöllisen julkisen taiteen maisemassa / Heidi Hänninen / KAS! Kontula Art School -- From the Trees, With Love / Hanna Vahvaselkä -- Weather as a Gift: From Divine Favour to Resonant Dialogues / Juan C. Duarte Regino -- Embrace (of) the Gift / Harri Laakso -- Bios.
Keywords: Art; Art--Research.; Gifts.; Aesthetics; Art--Philosophy.; taide; taiteellinen tutkimus; lahjat; estetiikka; taiteellinen työ; taidefilosofia